Marine habitat use and movement in response to ocean warming by a threatened forest-nesting seabird - Marie-Sophie Garcia-Heras; Christopher Wolf; Jennifer A. Bailey Guerrero; Lindsay J. Adrean; S. Kim Nelson; Daniel D. Roby; Matthew G. Betts; James W. Rivers (Global Ecology and Conservation, 2024)
Although anthropogenic climate change has resulted in significant alterations of ocean environments, the degree to which marine organisms can respond behaviorally to climate effects remains poorly understood, especially for species with increased extinction risk. We monitored marine space use and movement of the threatened marbled murrelet (Brachyramphus marmoratus) along the central coast of Oregon, USA during the 2017–2019 breeding seasons to quantify marine habitat selection patterns across a range of ocean conditions. We hypothesized that marine locations characterized by upwelling, nearshore areas adjacent to old-growth forest nesting habitat, and protected marine areas would be preferentially selected by tagged birds. Using >4800 locations collected from >180 individuals, we found that murrelets selected areas near small estuaries and with localized upwelling (as characterized by decreased sea-surface temperatures and high salinity), both of which are expected to lead to greater food availability during periods when sea-surface temperatures are elevated and coastal upwelling is reduced (i.e., poor ocean conditions). In addition, we found that individuals did not preferentially select marine areas adjacent to potential old-growth nesting habitat, and that murrelets exhibited limited overlap with protected marine areas regardless of ocean conditions. Unexpectedly, the majority (62%) of tagged individuals moved beyond the boundaries of our 135-km long study area in the year with the poorest ocean conditions (2017), with 15% of birds moving >500 km from their capture location. Our results confirm that marine habitat selection in murrelets becomes decoupled from terrestrial nesting habitat during periods of poor ocean conditions, and that such conditions are associated with low breeding propensity and long-distance movements during the breeding season. In addition to demonstrating murrelets undertake fine- and coarse-scale movements to buffer against poor ocean conditions, our study also emphasizes the importance of considering broad spatial scales in the marine environment when undertaking measures to conserve murrelet populations.